2008
DOI: 10.1258/rsmmsl.48.3.211
|View full text |Cite
|
Sign up to set email alerts
|

Referrals for expert psychiatric opinion on dangerous offenders: a survey of instructions regarding defendants liable on conviction to a statutory assessment of dangerousness

Abstract: The Criminal Justice Act 2003 ('the Act') introduced significant changes to the sentencing of violent and sexual offenders. The Act brought in a statutory assessment of dangerousness which includes a statutory assumption of dangerousness ('SAD') for certain repeat offenders. Previously, expert psychiatric witnesses have commented on whether a defendant demonstrated sufficient mental instability to warrant a discretionary life sentence. Under this regime, psychiatric evidence is adduced to the assessment of dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Despite the importance of the assessment of dangerousness in such cases, solicitors appear very poor at explaining the evidential requirements to psychiatrists. In a survey of two years of medicolegal referrals to a regional secure unit, Bickle and Stankard (2008) found that in four-fifths of cases concerning alleged repeat violent or sexual offenders, the solicitors commissioning a psychiatric report made no request to comment on risk or dangerousness. In only a tiny fraction was the expert guided to the assessment of dangerousness in the statute.…”
Section: Prisonmentioning
confidence: 99%
“…Despite the importance of the assessment of dangerousness in such cases, solicitors appear very poor at explaining the evidential requirements to psychiatrists. In a survey of two years of medicolegal referrals to a regional secure unit, Bickle and Stankard (2008) found that in four-fifths of cases concerning alleged repeat violent or sexual offenders, the solicitors commissioning a psychiatric report made no request to comment on risk or dangerousness. In only a tiny fraction was the expert guided to the assessment of dangerousness in the statute.…”
Section: Prisonmentioning
confidence: 99%